Response to amoxicillin and perampanel in infantile Alexander disease - Susana Boronat; Eulalia Turon‐Viñas; Noel Mac Manus; Asuncion Diaz‐Gomez; Mónica Vicente; Victoria Ros‐Castelló; Alba Sierra‐Marcos (Epilepsia Open)
Abstract Type I Alexander disease (AxD) presents with paroxysmal neurodegeneration, refractory epilepsy, and encephalopathy in the first years of life and is associated with a poor prognosis. Although there is no treatment, mild symptomatic improvement has been reported in one case of adult Alexander treated with ceftriaxone, given its interaction with the mutant glial fibrillary acid protein (GFAP) responsible for the disease's pathogenesis. We describe a patient presenting with irritability starting at 2 months of age, initially attributed to gastroesophageal reflux. A ventriculoperitoneal shunt was placed at 3 months of age due to hydrocephalus secondary to aqueduct stenosis detected through an MRI scan, but the irritability persisted. At 5 months, a new brain MRI was performed due to irritability worsening, onset of abnormal ocular movements and seizures. In addition genetic testing was performed. AxD was diagnosed due to the mutation c.716G>A (p.Arg239His) in GFAP. Since irritability had worsened and had not responded to levomepromazine, treatment with amoxicillin (80 mg/kg/day) was attempted to modulate glutamate levels. The patient showed a striking improvement of irritability in 48 h that persisted over the next months. The patient had frequent daily seizures which did not respond to valproate, clonazepam, or phenobarbital. Perampanel, a postsynaptic AMPA receptor antagonist, was added to phenobarbital and he was seizure free for more than 3 months. Drugs modulating glutamate levels in the central nervous system, including β‐lactam antibiotics and perampanel, may have an important role in the symptomatic treatment of AxD and other neurodegenerative diseases where glutamatergic excitotoxicity is a pathogenic determinant. Plain Language Summary Alexander disease is a rare and serious condition that affects the brain, often leading to neurodegeneration (brain damage), seizures, and other problems in early childhood. The disease is caused by a mutation in a gene called GFAP. There is no cure, and current treatments mainly focus on relieving symptoms. This article discusses the case of a baby who showed signs of irritability and seizures from a young age. The baby was diagnosed with Alexander disease after brain scans and genetic testing. Despite treatment with various drugs, the baby continued to experience seizures and irritability. The doctors decided to try amoxicillin, a common antibiotic, because of its potential to help control the disease by affecting a brain chemical called glutamate. Surprisingly, the baby's irritability improved within 2 days of starting amoxicillin, and the improvement lasted for several months. However, the seizures persisted until another medication, perampanel, was added. This combination controlled the baby's seizures for over 3 months. Unfortunately, the baby passed away at 13 months due to complications from the disease. However, doctors believe that drugs like amoxicillin and perampanel could be promising treatments for managing symptoms of Alexander disease and other similar brain conditions in the future, especially where excess glutamate plays a role in the damage. This case suggests that these treatments may help control irritability and seizures, offering hope for better management of this challenging disease.